2006
DOI: 10.1017/cbo9780511607523
|View full text |Cite
|
Sign up to set email alerts
|

Changing White Attitudes toward Black Political Leadership

Abstract: Changing White Attitudes toward Black Political Leadership Despite the hopes of the civil rights movement, researchers have found that the election of African Americans to office has not greatly improved the well-being of the black community. By shifting the focus to the white community, this book finds that black representation can have a profound impact. Utilizing national public opinion surveys, data on voting patterns in large American cities, and more in-depth studies of Los Angeles and Chicago, Zoltan Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 233 publications
(181 reference statements)
1
81
1
Order By: Relevance
“…Electoral data suggests that minorities, especially Asians and Latinos, remain underrepresented in elected office (Hajnal, 2010), and that there is disparity in the racial composition of electorates that elect minority candidates, with most black and Latino representatives coming from majority minority districts. Asians are the notable exception to this trend, as most Asian representatives are elected in majority white areas (Hajnal, 2007). The thrust of the literature has focused on black candidates, and several prominent studies have found that black candidates fare worse among white voters when paired against white candidates (Terkildsen, 1993;Reeves, 1997;Bullock and Dunn, 1999).…”
Section: Minority Candidates and Vote Choicementioning
confidence: 99%
See 4 more Smart Citations
“…Electoral data suggests that minorities, especially Asians and Latinos, remain underrepresented in elected office (Hajnal, 2010), and that there is disparity in the racial composition of electorates that elect minority candidates, with most black and Latino representatives coming from majority minority districts. Asians are the notable exception to this trend, as most Asian representatives are elected in majority white areas (Hajnal, 2007). The thrust of the literature has focused on black candidates, and several prominent studies have found that black candidates fare worse among white voters when paired against white candidates (Terkildsen, 1993;Reeves, 1997;Bullock and Dunn, 1999).…”
Section: Minority Candidates and Vote Choicementioning
confidence: 99%
“…Sigelman et al (1995) finds that blacks and Latinos are stereotyped as being unable to manage major policy issues. Hajnal (2007) finds that among black challengers, stereotypes about incompetence are especially pervasive, which leads to a voting backlash among whites.…”
Section: When Does Race Matter?mentioning
confidence: 99%
See 3 more Smart Citations